Lactancia materna como antecedente en el rendimiento académico de los estudiantes de la Escuela Zoila Ugarte de Landivar de la parroquia Pozul del cantón Celica. - Astudillo Romero, Johanna Maribel (2016)
For several decades the scientific literature on the relationship between breastfeeding and infant neurodevelopment has grown. Breast milk could therefore influence the child's academic performance by promoting optimal spatial growth and brain development. This is why it was considered appropriate to carry out this study called: "BREASTFEEDING AS ANTECEDENT IN THE ACADEMIC PERFORMANCE OF THE STUDENTS OF THE ZOILA UGARTE SCHOOL OF LANDIVAR OF THE PARISH OF POZUL DEL CANTÓN CELICA", whose general objective was: To identify breastfeeding as antecedent in the academic performance of the students of the Zoila Ugarte School of Landivar of the parish of Pozul del Cantón Celica, were also raised as specific objectives: To establish the frequency of exclusive breastfeeding within the first six months of age, relationship between breastfeeding time and school performance, and to know the difference in school performance in those who received exclusive breastfeeding and other types of feeding. For this, a descriptive cross-sectional study was carried out. The sample included 130 students from 7 to 12 years of age. A survey was applied to mothers to determine the existence of breastfeeding, duration of breastfeeding, and use of milk formula. In children, school performance was assessed by grade point average. It was found that 93% of the children received breast milk, of them 76% exclusive breastfeeding for 6 months, while only 7% artificial feeding tube. 68% who received exclusive breast milk for 6 months dominated learning, while those who breastfed for two or less months achieved the required learning in 67% without mastering them. These findings allow us to affirm that breastfeeding positively influences academic performance. Key Words: Breastfeeding, antecedent, academic performance